2016
DOI: 10.1097/mph.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Blackfan Anemia: A Nonclassical Patient With Diagnosis Assisted by Genomic Analysis

Abstract: Summary Diamond Blackfan anemia (DBA) is an inherited syndrome usually presenting with severe macrocytic anemia in infancy, paucity of erythroid precursors in the bone marrow, and congenital anomalies. We describe a child with mild, transfusion independent normocytic anemia whose diagnosis of DBA was established by identification of a novel de novo mutation disrupting normal splicing of the ribosomal protein RPL5. The diagnosis of DBA was confirmed by elevated erythrocyte adenosine deaminase levels and an abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…[ 22 ] There are mounting pieces of evidence of diagnosing of the nonclassical presentation of DBA and generates more apprehension. [ 4 82 , 83 ] In the current case, the focal evidence for the determination of DBA was the persistent isolated anemia, and normal marrow cellularity with markedly depressed erythropoiesis was in the same as mentioned earlier study report. [ 84 ] DBA patients with late-onset anemia or a relatively mild course have been reported.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[ 22 ] There are mounting pieces of evidence of diagnosing of the nonclassical presentation of DBA and generates more apprehension. [ 4 82 , 83 ] In the current case, the focal evidence for the determination of DBA was the persistent isolated anemia, and normal marrow cellularity with markedly depressed erythropoiesis was in the same as mentioned earlier study report. [ 84 ] DBA patients with late-onset anemia or a relatively mild course have been reported.…”
Section: Discussionsupporting
confidence: 79%
“…[ 84 ] DBA patients with late-onset anemia or a relatively mild course have been reported. [ 82 85 ] Multiple previous studies showed that a meager number of patients were identified as DBA cases after 12 months of age, with insignificant anemia requiring treatment or intervention at all. [ 6 13 , 86 87 88 89 ] The present case, along with those previously reported, highlights the phenotypic heterogeneity of DBA and the prerequisite to contemplate this illness even in patients with no evident congenital glitches and only a distinctly drop of red cell precursors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistent findings from human model cellular systems and cell lines (4,(14)(15)(16)) are yet to be reconciled, and it remains unclear whether additional mechanisms may contribute to erythroid failure in DBA (17). Furthermore, although the diagnostic criteria of DBA include presentation in infancy with virtually no mature bone marrow erythroblasts (EBs) (3), atypical presentations in later life with milder hematological manifestations are not uncommon (18)(19)(20)(21)(22). The mechanisms underpinning these heterogeneous clinical phenotypes are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This effect could also contribute to the pathogenicity of the p.S138F variant. We conclude that expression of the p.S138F variant in the DBA patient reported in a Japanese cohort (Wang et al, 2015) affects ribosome synthesis and results in a deficit -Shemer et al, 2016). Some patients are diagnosed later in life with mild anemia requiring no therapy (Gazda et al, 2008).…”
Section: Discussionmentioning
confidence: 67%